2011
DOI: 10.1128/aac.01209-10
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntiretroviral Properties of S/GSK1349572, a Next-Generation HIV Integrase Inhibitor

Abstract: S/GSK1349572 is a next-generation HIV integrase (IN) inhibitor designed to deliver potent antiviral activity with a low-milligram once-daily dose requiring no pharmacokinetic (PK) booster. In addition, S/GSK1349572 demonstrates activity against clinically relevant IN mutant viruses and has potential for a high genetic barrier to resistance. S/GSK1349572 is a two-metal-binding HIV integrase strand transfer inhibitor whose mechanism of action was established through in vitro integrase enzyme assays, resistance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
338
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(372 citation statements)
references
References 36 publications
30
338
1
3
Order By: Relevance
“…While resistance mutations were detected within 29 weeks under either DTG or EVG selection pressure, no resistance mutations emerged under pressure with RAL. A direct comparison cannot be drawn between our selection studies, which were performed using rhesus PBMCs, and those performed by others who used HIV-1 in MT-2 cell lines and showed that mutations emerged rapidly under RAL pressure (31,46). Our selection experiments with RAL may suggest that RAL possesses a higher genetic barrier than the other INSTIs in rhesus macaques; however, a previous study revealed that SHIV-infected macaques treated with pressure from L-870812, a RAL analogue, possessed the N155H substitution after 25 days of treatment with this drug (36).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While resistance mutations were detected within 29 weeks under either DTG or EVG selection pressure, no resistance mutations emerged under pressure with RAL. A direct comparison cannot be drawn between our selection studies, which were performed using rhesus PBMCs, and those performed by others who used HIV-1 in MT-2 cell lines and showed that mutations emerged rapidly under RAL pressure (31,46). Our selection experiments with RAL may suggest that RAL possesses a higher genetic barrier than the other INSTIs in rhesus macaques; however, a previous study revealed that SHIV-infected macaques treated with pressure from L-870812, a RAL analogue, possessed the N155H substitution after 25 days of treatment with this drug (36).…”
Section: Discussionmentioning
confidence: 68%
“…Viruses under RAL selective pressure did not select for any substitutions. E92Q is the most frequent substitution in HIV-1-infected individuals treated with EVG (28-30) and confers high levels of resistance against this compound (31).…”
Section: Effect Of Integrase Substitutions On Viral Infectivitymentioning
confidence: 99%
“…Some mutations in integrase that are potentially involved in resistance to DTG were reported at positions F121, S153, G118, E138, and R263 in vitro and in vivo (Kobayashi et al 2011;Quashie et al 2013b). R263K was initially reported as the most common substitution identified in cell culture selections with DTG and was shown to confer only moderate resistance to DTG (fold change = 2.3-fold) (Quashie et al 2012).…”
Section: The Unique Hiv Drug Resistance Profile Of Dtgmentioning
confidence: 99%
“…These properties are probably responsible for the effectiveness of DTG against most RAL/EVG resistant strains, although viruses containing E138K, G140S or Q148H mutations had lower susceptibility [Quashie et al 2012b]. Exposure to DTG in selection studies can cause changes in the viral genome at positions E92, L101, T124, S153 and G193 [Kobayashi et al 2011]. However, susceptibility fold changes are moderate (<2.5) for all these substitutions.…”
Section: Insti Resistance Patternmentioning
confidence: 99%